Review of the article "Laboratory of structure of technical dissertation in a classroom on violence in the field" - Moreira, Jhoanna D’Arc Araújo; Alvarenga, Cleonice Felicia de (Revista Coleta Científica, 2018)
This is a review of the article entitled “Laboratory of the structure of the technical dissertation in the classroom on violence in the field”. This article is authored by: Jonas Rodrigo Gonçalves et al. The article reviewed here was published in the journal “Revista JRG de Estudos Acadêmicos”, in Year I, Vol. 1, n.1, 2018.